2019
DOI: 10.1186/s11671-019-3042-7
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Resveratrol-Loaded Solid Lipid Nanoparticle Improves Insulin Resistance Through Targeting Expression of SNARE Proteins in Adipose and Muscle Tissue in Rats with Type 2 Diabetes

Abstract: In the current study, we developed resveratrol (RES)-loaded solid lipid nanoparticle (SLN-RES) in order to improve insulin resistance through the upregulation of SNARE protein complex in rats with type 2 diabetes. The SLN-RES characteristics include the following: the average size of 248 nm, the zeta potential of − 16.5 mV, and 79.9% RES entrapment efficiency. The release profile of SLN-RES showed an initial burst followed by a sustained release in natural condition. Infrared spectroscopy results revealed good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…RSV molecules are highly stable when they are entrapped in SLN, thereby protecting RSV from degradation in biochemical reactions [32]. Additionally, the potential penetrating ability and cell uptake capacity of RSV-SLN affect the tissue accumulation of RSV that may be responsible for the effects of RSV-SLN in muscle tissue [15]. We mainly explored the improved protective effects and underlying mechanism of RSV-SLN on endurance performance and focused on the mitochondrial QC process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RSV molecules are highly stable when they are entrapped in SLN, thereby protecting RSV from degradation in biochemical reactions [32]. Additionally, the potential penetrating ability and cell uptake capacity of RSV-SLN affect the tissue accumulation of RSV that may be responsible for the effects of RSV-SLN in muscle tissue [15]. We mainly explored the improved protective effects and underlying mechanism of RSV-SLN on endurance performance and focused on the mitochondrial QC process.…”
Section: Discussionmentioning
confidence: 99%
“…SLNs, which can be metabolized by many organisms, can modulate drug release [11][12][13]. SLNs can efficiently protect encapsulated resveratrol drugs in the biological environment and improve their physiochemical properties [14][15][16]. Hence, this study evaluated the effect of RSV-loaded SLN (RSV-SLN) supplementation on exercise performance to explore its possible mechanisms.Maintaining mitochondrial function involves mitochondrial biogenesis, mitophagy, fusion, and fission.…”
mentioning
confidence: 99%
“…Another research report informs about improving insulin resistance by improving the expression of visfatin and RES feeding has improved the expression of glucose transporter GLUT2 and 4 in rats which are induced with diabetes [177]. Hence, RES was encapsulated in SLNs and tested the following parameters, such as fasting blood sugar (FBS), insulin, and oxidative stress in type II diabetes-induced rats [178].…”
Section: Treatment Of Insulin Resistance In Type 2 Diabetes With Resvmentioning
confidence: 99%
“…The SLN-RES nanoparticles that were prepared [178] had an average of 248 nm in size, zeta potential at 16.5 mV, and with a RES entrapment efficiency of 79.9%. These nanoparticles with RES had a sustained release of RES and hence had good bioavailability for RES.…”
Section: Treatment Of Insulin Resistance In Type 2 Diabetes With Resvmentioning
confidence: 99%
“…Administration of Res-SLNs significantly decreased oxidative stress and inhibited weight loss. Investigation of molecular signaling pathways demonstrated that Res-SLNs are capable of the up-regulation of SNARE resulting in attenuation of DM [23]. DM harmfully affects reproductive function.…”
Section: Introductionmentioning
confidence: 99%